Hedotettix angulatus sp. nov. (Orthoptera: Tetrigoidea:Tetrigidae, Tetriginae) a new pygmy grasshopper species from India - Gupta, Sunil Kumar; Shi, Jian-Ping; Chandra, Kailash (Zootaxa, 2016)
Hedotettix angulatus sp. nov. is described from Chhattisgarh, India. The new species is similar to Hedotettix grossus Hancock, 1915, it differs from the latter by (i) anterior margin of vertex angulate, (ii) ovipositor robust, length of upper valves 2.2 times its width, (iii) antennal grooves situated above the lower margin of the compound eyes, (iv) median carina of vertex strong and extended up to the posterior end of depression, (v) facial carinae are all most parallel, (vi) frontal costa bifurcation starts in about ¼ of the compound eye height, (vii) anterior margin of middle carina of pronotum depressed. A key to known species of the genus Hedotettix from the Indian subcontinent is provided. Type specimens are deposited in the Central Entomological Laboratory (CEL) of the Zoological Survey of India, Kolkata.